Development of a single-dose Q fever vaccine with an injectable nanoparticle-loaded hydrogel: effect of sustained co-delivery of antigen and adjuvant - Lu Wang; Aaron Ramirez; Jiin Felgner; Enya Li; Jenny E. Hernandez-Davies; Anthony E. Gregory; Philip L. Felgner; Ali Mohraz; D. Huw Davies; Szu-Wen Wang (Drug Delivery)
Q fever is a zoonotic infectious disease caused by Coxiella burnetii, and there is currently no FDA-approved vaccine for human use. The whole-cell inactivated vaccine Q-VAX, which is only licensed in Australia, has a risk of causing severe adverse reactions, making subunit vaccines a good alternative. However, most subunit antigens are weak immunogens and require two or more immunizations to elicit an adequate level of immunity. We hypothesized that by combining a nanoparticle to co-deliver both a protein antigen and an adjuvant, together with a hydrogel depot for sustained-release kinetics, a single-administration of a nanoparticle-loaded hydrogel vaccine could elicit a strong and durable immune response. We synthesized and characterized a protein nanoparticle (CBU-CpG-E2) that co-delivered the immunodominant protein antigen CBU1910 (CBU) from C. burnetii and the adjuvant CpG1826 (CpG). For sustained release, we examined different mixtures of PLGA-PEG-PLGA (PPP) polymers and identified a PPP solution that was injectable at room temperature, formed a hydrogel at physiological temperature, and continuously released protein for 8 weeks in vivo. Single-dose vaccine formulations were administered to mice, and IgG, IgG1, and IgG2c levels were determined over time. The vaccine combining both the CBU-CpG-E2 nanoparticles and the PPP hydrogel elicited a stronger and more durable humoral immune response than the soluble bolus nanoparticle vaccines (without hydrogel) and the free antigen and free adjuvant-loaded hydrogel vaccines (without nanoparticles), and it yielded a balanced IgG2c/IgG1 response. This study demonstrates the potential advantages of using this modular PPP hydrogel/nanoparticle system to elicit improved immune responses against infectious pathogens.